Characterization Of The Response Of Synthetic Bone Substitute To Compressive Load - Zamzuri, Hamedon; M. S. M., Sani (2009)
Synthetic bone substitute has been used for bone implantation in humans. Chemical composition of this bone substitute is claimed to be close to that of human bone. The objective of this research is to characterize the response of synthetic bone substitute after subjected to compressive load. Compression test was carried out on INSTRON Universal Tester. The maximum load that the specimen can endure and stress-strain response were obtained from the compression experiment. Qualitative and quantitative characterization was done using scanning electron microscope and image analyzer. The response of the specimen showed multiple yield points during compression. Stress-strain response did not follow any of the response of either ductile or brittle materials. The response was rather strictly nonlinear throughout the test range undergone. In addition, the mode of failure is more to shear. The micrographs reveal porosity range, chemical composition and the smallest cell size sustained after compression. The results of this research can be useful for developing new synthetic bone or at least improving the properties of the current one.